IMPLEMENTASI KEBIJAKAN PANGKASEPNA (PENGURANGAN KEMUBAJIRAN BIAYA POKOK PRODUKSI DAN NAC) PADA KANTOR PT PLN (PERSERO) UNIT INDUK TRANSMISI JAWA BAGIAN TENGAH - Salsa Maulida (Fisip UIN Sunan Gunung Djati Bandung, 2024)
The purpose of the author conducting this research is to find out how the implementation of the PANGKASEPNA policy at the Office of PT PLN (Persero) Central Java Transmission Main Unit, with descriptive qualitative research methods, the results of this study indicate that the PANGKASEPNA policy at the Office of PT PLN (Persero) UIT JBT has been established and implemented since April 10, 2023 with the aim of identifying and reducing waste in the production and operational processes, as well as optimizing the use of available resources. By using the dimensions according to Edward III, namely, communication, resources, disposition or attitude of implementers, and bureaucratic structure. In implementing the PANGKASEPNA policy, the Ranger Leader who leads the COC (Code of Conduct) will fill in material regarding the efficiency of BPP and NAC which is then realized through all employees, then weekly evaluations will be carried out (supervision and evaluation of AO absorption), and guidance will be given by the HST Head Office division in controlling operational costs. In addition, the NAC component at the Office of PT PLN (Persero) UIT JBT is divided into four aspects including consumption costs, SPPD, stationery purchases, and printed matter. Thanks to the implementation of the PANGKASEPNA culture, the Office of PT PLN (Persero) UIT JBT received the best business unit award in the category of budget management and reporting.